2014
DOI: 10.1177/0961203314559085
|View full text |Cite
|
Sign up to set email alerts
|

Matrix metalloproteinase 9 polymorphisms and systemic lupus erythematosus: correlation with systemic inflammatory markers and oxidative stress

Abstract: Systemic lupus erythematosus (SLE) is an autoimmune disease that involves multiple organs and is characterized by persistent systemic inflammation. Among the effects of inflammatory mediators, the induction of matrix metalloproteinases-2 and -9 (MMP-2 and MMP-9) and oxidative stress has been demonstrated to be important in the development of SLE. In this study, the possible association between MMP-9 and MMP-2 functional promoter polymorphism, stress, and inflammatory markers with development of severe cardiova… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 38 publications
(82 reference statements)
2
30
1
Order By: Relevance
“…Other antibodies with pathogenic relevance to cognitive dysfunction include anti-cardiolipin antibodies (ACL), anti-neuronal antibodies, anti-endothelial-cell antibodies (AECAs) and anti- Nedd5 C-ter antibodies 8-10. Patients with systemic lupus erythematosus (SLE) who have neuropsychiatric involvement were found to have significantly higher levels of matrix metalloproteinase-9 (MMP-9) in their serum and in cerebrospinal fluid (CSF), as compared to those without neuropsychiatric syndromes 11,12…”
Section: Introductionmentioning
confidence: 99%
“…Other antibodies with pathogenic relevance to cognitive dysfunction include anti-cardiolipin antibodies (ACL), anti-neuronal antibodies, anti-endothelial-cell antibodies (AECAs) and anti- Nedd5 C-ter antibodies 8-10. Patients with systemic lupus erythematosus (SLE) who have neuropsychiatric involvement were found to have significantly higher levels of matrix metalloproteinase-9 (MMP-9) in their serum and in cerebrospinal fluid (CSF), as compared to those without neuropsychiatric syndromes 11,12…”
Section: Introductionmentioning
confidence: 99%
“…MMP genetic polymorphisms and levels of gene expression have been associated with several diseases, including chronic obstructive pulmonary disease, coronary heart disease, rheumatoid arthritis, and systemic lupus erythematosus (Schirmer et al, 2009;Scherer et al, 2010;Bahrehmand et al, 2015;Jiang et al, 2016;Ma et al, 2015Ma et al, , 2016. Different studies have addressed the MMP serum levels and MMP gene expression in SSc (Young-Min et al, 2001;Kikuchi et al, 2002;Toubi et al, 2002;Meng et al, 2008;Brown et al, 2012;Frost et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Matrix metalloproteinase (MMP)-10 levels are known to be associated with severe atherosclerosis in patients with CKD and therefore could be used as a novel indicator. 6,7,28 Thus, MMP-9 could serve as an inflammatory marker, and MMP inhibitors may be used in the treatment of acute infections in geriatric patients. 24 We did not find any significant relation between MMP-9 levels and prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…26 Ma et al 27 showed the importance of inflammation in cardiac ageing and the role of MMP-9 in the direct and indirect polarization of the macrophages. Bahrehmond et al 28 found a correlation between MMP-9 and systemic inflammatory markers and oxidative stress in patients with systemic lupus erythematosus. Vondooren et al 29 stated that MMP inhibitors could be used in acute neurologic inflammation due to their known role in monomeric and multimeric forms in central nervous system infection and inflammation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation